2002
DOI: 10.1161/hy0302.104669
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Left Ventricular Hypertrophy in Hypertensive Patients Without and With Blood Pressure Control

Abstract: Abstract-Previous studies have shown that in the population, only a minority of treated hypertensive patients achieve blood pressure (BP) control. Whether and to what extent this inadequate control has reflection on hypertension-related organ damage has never been systematically examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
2
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 31 publications
8
42
2
10
Order By: Relevance
“…In our series, LVH prevalence was consistently higher than that found in studies conducted in population-based samples and in untreated hypertensives attending at specialist centres. 29,30 Our values, however, are in line with that reported (70%) in a large Spanish survey of 946 essential hypertensives from primary care centres. 31 Several factors may explain the high prevalence of LVH in our survey: (1) old age (less than 7% of our patients were o40 years); (2) duration of hypertension (less than 20% were untreated, that is, in the initial phase); moreover, up to 50% of patients had a previous echo examination and was reassessed for LVH regression; (3) non-standardized identification of LV interfaces due to the lack of a reading centre.…”
Section: Echocardiography In Hypertension C Cuspidi Et Alsupporting
confidence: 92%
“…In our series, LVH prevalence was consistently higher than that found in studies conducted in population-based samples and in untreated hypertensives attending at specialist centres. 29,30 Our values, however, are in line with that reported (70%) in a large Spanish survey of 946 essential hypertensives from primary care centres. 31 Several factors may explain the high prevalence of LVH in our survey: (1) old age (less than 7% of our patients were o40 years); (2) duration of hypertension (less than 20% were untreated, that is, in the initial phase); moreover, up to 50% of patients had a previous echo examination and was reassessed for LVH regression; (3) non-standardized identification of LV interfaces due to the lack of a reading centre.…”
Section: Echocardiography In Hypertension C Cuspidi Et Alsupporting
confidence: 92%
“…He showed that left ventricular mass index, left ventricular wall thickness, and prevalence of left ventricular hypertrophy were markedly increased not only in untreated hypertensive patients but also in treated hypertensives with inadequate blood pressure control, compared with values in the normotensive groups. Echocardiographic abnormalities were less in treated hypertensives with blood pressure control than in patients with inadequate blood pressure control, but values were still clearly greater than in normotensive subjects in the Mancia study [21]. Early interventions to prevent LVH in early stages of primary hypertension, and also to treat the other contributing diseases, seem to be more logical strategy.…”
Section: Discussionmentioning
confidence: 84%
“…The highest figures of echocardiographic LVH prevalence (475%) are reported in studies examining patients with resistant hypertension 35 and electrocardiographic evidence of LVH; 13 these studies include a significant fraction of patients with prior CV complications and the highest BP levels. Conversely, the lowest (o30%), although clinically relevant, rates of LVH are found in hypertensives surveyed in population-based studies 14,18,27 or in middle-aged, recently diagnosed, untreated hypertensives. 25,28,31,32,38 From these data, two considerations can be made: (1) a consistent fraction of treated hypertensive patients are still exposed to a high CV risk as antihypertensive treatment is unable to normalize BP and consequently reverse alterations in cardiac structure; (2) a noticeable portion of hypertensive patients (30%) enrolled in the examined studies were untreated, despite having a cardinal manifestation of organ damage such as LVH; this suggests that unsolved issues in primary prevention of CV disease include not only unsatisfactory BP control but also poor awareness of the hypertensive status and delay in hypertensive treatment.…”
Section: Discussionmentioning
confidence: 95%